2002
DOI: 10.1007/s11357-002-0001-4
|View full text |Cite
|
Sign up to set email alerts
|

Survival and cell mediated immunity after burn injury in aged mice

Abstract: The elderly are less able to survive burn injury than young healthy individuals. Regardless of age, burn victims often succumb to secondary infections rather than the primary injury. Since immune responses diminish with age, it is likely that aged individuals are predisposed to a poor outcome by virtue of their weak immune system. Elevated production of macrophage-derived mediators, including interleukin-6 (IL-6), may lead to post-injury immunosuppression in young adults. Healthy aged individuals produce high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 50 publications
7
37
0
1
Order By: Relevance
“…Consistent with our previous findings (25), young mice were able to mount a normal DTH response, regardless of injury ( Fig. 1).…”
Section: Dth Response After Burn Traumasupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with our previous findings (25), young mice were able to mount a normal DTH response, regardless of injury ( Fig. 1).…”
Section: Dth Response After Burn Traumasupporting
confidence: 92%
“…Consequently, a great deal of research has focused on the immune response after injury and its deficiencies. Our laboratory has recently shown that increased mortality in a murine dorsal scald model is associated with decreases in DTH response and T-cell proliferation (25). Herein, we expand on the previous studies to describe possible mechanisms for the altered immune response in the aged following injury, by examining both in vivo (DTH) and in vitro (splenocyte proliferation and cytokine production) responses to stimulation.…”
Section: Discussionmentioning
confidence: 92%
“…Aging is associated with systemic immune dysfunction known as "inflamm-aging", often manifesting as increased levels of tissue and circulating proinflammatory cytokines [36][37][38] (eg, interleukins IL-1b and IL-6, tumor necrosis factor-a) in the absence of an immunologic threat, as well as concomitant "immunosenescence" or a blunted response to pathogenic threat or tissue injury. 5,39 The 2 phenomena are closely related, and the imbalance in immune mediators, which results in a proinflammatory state at baseline seems to play a role in the age-related destruction of lung parenchyma.…”
Section: Immune Mediatorsmentioning
confidence: 99%
“…This improved survival was accompanied by a diminution in the serum levels of IL-6 . Additionally, we have reported that estrogen treatment partially restored the delayed-type hypersensitivity response , a systemic cellular immune response previously described to be markedly attenuated in aged mice after burn injury (Kovacs et al, 2002;Plackett et al, 2003).…”
Section: Discussionmentioning
confidence: 67%
“…Mice were subjected to a 15% TBSA dorsal scald or sham injury as previously described (Faunce et al, 1997), with modification (Kovacs et al, 2002). In brief, after induction of anesthesia (Nembutal 40 mg/kg of animals weight, intraperitoneally (i.p.…”
Section: Induction Of Injury and Exposure To Lipopolysaccharidementioning
confidence: 99%